Conversion of glycerol to glycerol carbonate via transesterification using 1-Ethyl-3-Methylimidazolium acetate catalyst / Zati Ismah Ishak - Zati Ismah, Ishak (2018)
In the present research, the synthesis of glycerol carbonate by transesterification of glycerol with diethyl carbonate in a green and efficient process catalyzed by ionic liquid was comparatively studied. A series of imidazolium and ammonium-based ionic liquids with different anions and conditions optimization (reaction temperature, reaction time, diethyl carbonate/glycerol ratio, solvent and catalyst loading) were screened for the best catalytic activity towards glycerol carbonate synthesis with respect to glycerol conversion and glycerol carbonate yield. It has been revealed that 1-ethyl-3-methylimidazolium acetate ([Emim][Ac]) remarks the highest activity towards glycerol conversion and glycerol carbonate yield of 93.5%, and 88.7%, respectively at 120 ᵒC, 2.0 hours, molar ratio of diethyl carbonate/glycerol of 2, 0.50 mol% [Emim][Ac] loading with 2.0 wt.% water content. The peak intensities at 1262 cm-1 and 923 cm-1 corresponding to O-H bending and 3387 cm-1 corresponding to O-H stretching in glycerol were reduced indicate to glycerol being converted to glycerol carbonate. Meanwhile, the peak at 1750 cm-1 corresponding to C=O and also peaks between 1200 cm-1 to 1000 cm-1 corresponding to C–C and C–O stretching of 2-hydroxyethyl chain showed an increase in intensity. These supported the presence of glycerol carbonate while reaction was in progress. Glycerol carbonate peaks at 61.5 ppm, 67.0 ppm, and 77.5 ppm corresponding to –CH2–O-, –CH2–OH and –CH–, respectively are gradually increased when the reaction solution turned into a single phase at 1.5 hours. Response surface methodology (RSM) showed the interactive effects between selected reaction parameters towards glycerol conversion and glycerol carbonate yield with 92.4% and 91.8%, respectively at optimum reaction conditions; reaction temperature of 118 ᵒC, at 1.8 hours with 2.2 of diethyl carbonate/glycerol ratio and 0.42 mol% [Emim][Ac] loading. Recyclability study showed insignificant reduction of glycerol conversion from recovered [Emim][Ac] indicating that [Emim][Ac] could be reused for approximately three times. All the respective peaks of [Emim][Ac] can be comparably resolved with little variation in chemical shift of 1H spectra NMR for each cycle, thus revealing that [Emim][Ac] was successfully recovered with no degradation on its structure. The result of the computational study using a General Atomic and Molecular Electronic Structure System (GAMESS) software clearly demonstrated that the activation of glycerol proceeds mainly through the hydrogen bonding interaction with [Ac]- anion. On the other hand, diethyl carbonate is also capable of forming hydrogen bonding with imidazolium ring proton at carbon 2 position and hydroxyl group of glycerol. The proposed mechanism of glycerol carbonate synthesis agreed well with the theoretical computational study.